2022
DOI: 10.1177/20503121221076370
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stillbirth among women who gave birth at Hiwot Fana Specialized University Hospital, Eastern Ethiopia: A facility-based cross-sectional study

Abstract: Introduction/objectives: Stillbirths are an adverse birth outcome and a significant public health problem in low- and high-income countries. Ethiopia is ranked seventh among ten countries that constitute 66% of the world’s stillbirths. However, there is a dearth of evidence about stillbirths and the determinants in the country, particularly in Eastern Ethiopia. Hence, this study aimed to assess the prevalence and determinants of stillbirths among women who gave birth at Hiwot Fana Specialized University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In this study, we found that 90% died in HAM maternity before the 7 th day of life, that is, during the perinatal period, with mainly being stillborn (73%). The magnitude of stillbirths observed in this study (3%) is in line with the studies conducted in Nigeria (4.8%) [45] and Tanzania (3.5%) [46] and lower compared with studies from Ethiopia (6.7%) [47]. Most stillbirths occurred during intrapartum, as also identified in LMICs similar to STP, and most could have been prevented [48,49].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that 90% died in HAM maternity before the 7 th day of life, that is, during the perinatal period, with mainly being stillborn (73%). The magnitude of stillbirths observed in this study (3%) is in line with the studies conducted in Nigeria (4.8%) [45] and Tanzania (3.5%) [46] and lower compared with studies from Ethiopia (6.7%) [47]. Most stillbirths occurred during intrapartum, as also identified in LMICs similar to STP, and most could have been prevented [48,49].…”
Section: Discussionsupporting
confidence: 88%
“…The fivefold higher risk of multiple pregnancies having ABO, can be associated with the fact that monochorionic pregnancies have a vascular anastomosis within the placenta, affecting the perfusion of each twin and promoting adverse outcomes such as preterm labor, premature rupture of membranes, antepartum hemorrhage and fetal death. Adverse outcomes in twin pregnancies were also reported in other studies [49,50]. Some studies describe that twin pregnancies have a thirteenfold increase in rates of stillbirth in monochorionic pregnancies and a five-fold increase in dichorionic twins compared with singleton pregnancies [51].…”
Section: Discussionsupporting
confidence: 57%
“…Some studies describe that twin pregnancies have a thirteen-fold increase in rates of stillbirth in monochorionic pregnancies and a five-fold increase in dichorionic twins compared with singleton pregnancies [51]. Hence, the association between multiple pregnancies and ABO in this study reveals the importance of screening for multiple pregnancies as one key component of ANC to reduce the risk of ABO [49]. Other interventions to reduce ABO related to twin pregnancies that can be recommended in STP are delivery at 37 weeks gestation in uncomplicated dichorionic twin pregnancies and delivery at 36 weeks in monochorionic pregnancies, as proposed by some authors [51].…”
Section: Discussionmentioning
confidence: 71%
“…4 Adverse perinatal outcomes include an overall <5 child mortality rate of 55 deaths per 1000 live births, and neonatal mortality was 30 deaths per 1000 live births 5 and the pooled prevalence of low birth weight was 17.3% 6 and stillbirths was 6.7%. 7 A study conducted in northwest Ethiopia in 2021 found that the overall prevalence of adverse perinatal outcomes was 19.4%. 8 According to a 2019 study in northwest Ethiopia, 46.5% of newborns delivered to women had unfavourable outcomes of severe pre-eclampsia and eclampsia, with 28.1% of those being stillbirths.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%